Diplomasi Pertahanan Indonesia Dalam Latihan Militer Multinasional Super Garuda Shield 2023 - Delta Muhammad Ragil Wijaya; Made Panji Teguh Santoso (SOCIA: Jurnal Ilmu-Ilmu Sosial, 2025)
This study examines Indonesia’s defense diplomacy in the 2023 multinational military exercise Super Garuda Shield (SGS), conducted amid the strategic rivalry between the United States and China in the Indo-Pacific. This rivalry challenges Indonesia to uphold its independent and active foreign policy principle while enhancing national defense capacity. The study employs a descriptive qualitative method using content analysis of official documents, press releases, and national and international media reports from the 2022–2023 period. The analytical framework applies defense diplomacy as the main lens and the Regional Security Complex Theory (RSCT) as the regional context. The findings reveal that SGS 2023, which involved 19 countries and more than 5,000 personnel, served dual functions: strengthening the Indonesian Armed Forces’ capacity through interoperability and joint operations, and expanding Indonesia’s multilateral defense networks. At the same time, the exercise reinforced Indonesia’s independent position consistent with Indonesia’s long-standing bebas-aktif (independent and active) foreign policy principle. This study contributes to the literature by framing SGS as a strategic soft power instrument of Indonesia’s defense diplomacy. Keywords: Super Garuda Shield, Indonesia, Indo-Pasific, Defence Diplomacy, Regional Security